Morning blue light treatment improves sleep complaints, symptom severity, and retention of fear extinction memory in post-traumatic stress disorder - Vanuk, John R.; Pace-Schott, Edward F.; Bullock, Ayla; Esbit, Simon; Dailey, Natalie S.; Killgore, William D. S. (Frontiers in Behavioral Neuroscience, 2022)
Disrupted sleep is a major feature in numerous clinical disorders and is related to decrements in affective memory processing. The prevalence of sleep disruption in post-traumatic stress disorder (PTSD) is suggested to be a key feature that exacerbates the impaired ability to recall extinction memories during experimental fear conditioning. We hypothesized that an intervention employing blue-wavelength light therapy (BLT) to regulate sleep and stabilize circadian rhythms in patients with PTSD (i.e., via regulated morning exposure) would be associated with PTSD symptom improvement, decreased sleep-related complaints, as well as improved consolidation and retention of extinction memories relative to a fear conditioning/extinction paradigm. Eighty-two individuals with PTSD underwent a well-validated fear conditioning/extinction protocol with subsequent assignment to receive morning BLUE (BLT) or placebo AMBER (ALT) light therapy daily for 30-minutes over 6-weeks. Participants returned after the intervention for post-treatment extinction recall, comprised of exposure to the previously conditioned stimuli, with the difference in skin conductance response between the “extinguished” and the “never-extinguished” stimuli at follow-up. Participants also viewed previously conditioned stimuli in a novel context during a functional magnetic resonance imaging (fMRI) scan. BLUE light therapy was associated with improvements relative to correlated decreases between PTSD symptoms and sleep-related complaints. Participants receiving BLT also sustained retention of the extinction memory, while those in the placebo amber light treatment group showed impairment, characterized by the restoration of the extinguished fear response after 6-weeks. Participants in the ALT also demonstrated greater reactivity in the left insula when viewing the previously extinguished fear-conditioned stimuli in a novel context. Daily BLUE-wavelength morning light exposure was associated with greater retention of extinction learning in patients with PTSD when compared to ALT, as supported by both autonomic and neurobiological reactivity. We speculate that improved sleep facilitated by a stabilized circadian rhythm, after fear-learning, led to greater consolidation of the fear extinction memory, decreased PTSD symptom presentation, and associated decreases in sleep-related complaints. Prominent exposure treatments for PTSD incorporate principles of fear extinction, and our findings suggest that blue light treatment may facilitate treatment gains by promoting the consolidation of extinction memories via improved sleep.